2020
DOI: 10.1007/s00423-020-01946-4
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy in pancreatic cancer: what is the true oncological benefit?

Abstract: Background Neoadjuvant therapies (neoTx) have revolutionized the treatment of borderline resectable (BR) and locally advanced (LA) pancreatic cancer (PCa) by significantly increasing the rate of R0 resections, which remains the only curative strategy for these patients. However, there is still room for improvement of neoTx in PCa. Purpose Here, we aimed to critically analyze the benefits of neoTx in LA and BR PCa and its potential use on patients with resectable PCa. We also explored the feasibility of arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The therapeutic goal is to be able to select the patients with a favorable tumor biology, to justify cumbersome surgery with prospects of an oncologic and survival benefit. The obvious necessity to find biomarkers to assess the aggressivity of the tumor beyond anatomical landmarks and beyond the conventional radiological findings is the instigator to start a prospective study evaluating the role of radiomics, genomics and proteomics in the selection of patients with BR and LA after neoadjuvant FOLFIRINOX (PeRFormanCe Trial, NCT05298722) [ 33 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic goal is to be able to select the patients with a favorable tumor biology, to justify cumbersome surgery with prospects of an oncologic and survival benefit. The obvious necessity to find biomarkers to assess the aggressivity of the tumor beyond anatomical landmarks and beyond the conventional radiological findings is the instigator to start a prospective study evaluating the role of radiomics, genomics and proteomics in the selection of patients with BR and LA after neoadjuvant FOLFIRINOX (PeRFormanCe Trial, NCT05298722) [ 33 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although conventional neoadjuvant therapy has been able to downstage tumors in locally advanced and borderline resectable tumors, multi-omics tumor profiling of tumor biopsies before targeted neoadjuvant treatment has shown great promise and may result in optimal patient selection for systemic therapies, less-extensive surgical procedures due to maximized tumor shrinkage, or even lead, in the long term, to a wait-and-see approach in patients with PDAC with complete response to molecular-driven therapies [3]. We have recently reviewed and summarized the currently ongoing trials employing neoadjuvant therapy in human PDAC [17].…”
Section: Improving the Outcome Of Resectable Pdac Through Molecular Subtypingmentioning
confidence: 99%
“…Downloaded from Pancreas antitumour abilities. [20][21][22][23] Multiple studies have consistently reported better response rates and prolonged survival among women undergoing anticancer treatments, including nCRT. [24][25][26][27][28][29] Inititally, these beneficial outcomes were ascribed to reduced exposure to risk factors or enhanced pharmacokinetic drug handling.…”
Section: Introductionmentioning
confidence: 99%